À espera na urgência: uma perspetiva sociológica - Paula, João Miguel Pulquério de (2021)
Nesta investigação procura-se compreender as experiências do tempo (social) “à espera” em contexto hospitalar. O estudo deste fenómeno é tido como inovador pois a “espera” surge amiúde no quotidiano de todos, não obstante é um objeto pouco explorado em termos científicos. O setting a observar é a sala de espera de umas urgências hospitalares dado que apresenta características particulares para uma compreensão profunda deste fenómeno social. A opção metodológica é baseada na perspetiva etnográfica, objetivando descrever e analisar as práticas e interações sociais, assim como as experiências subjetivas do tempo resultantes desta vivência idiossincrática da espera. Objetiva-se incluir os componentes do tempo social na análise da espera, recentrando este fenómeno à luz da análise sociológica e sugerir algumas estratégias que permitam uma melhor gestão do tempo “à espera”; “Waiting in an emergency room”: a sociological perspective Abstract: This investigation seeks to understand the experiences of (social) time in a hospital context. The study of this phenomenon is seen as innovative because “waiting” is present in everyone's daily life, although it is an object not largely explored in scientific terms. The setting to be observed is the waiting room for hospital emergencies as it has particular characteristics for a profound understanding of this social phenomenon. The methodological option is based on an ethnographic perspective, aiming to describe and analyze social practices and interactions, as well as the subjective experiences resulting from this idiosyncratic experience of “waiting time”. The aim is to include the components of social time in the analysis of “wait”, refocusing this phenomenon in the light of sociological analysis, and to suggest some strategies that allow better management of the “waiting” time.